Serum vitamin D and obesity among US adolescents, NHANES 2011–2018 - Chen, Zisu; Qiu, Xiaojin; Wang, Qiong; Wu, Jing; Li, Min; Niu, Wenquan (Frontiers in Pediatrics, 2024)
Background and Objectives: Childhood obesity is highly prevalent worldwide. We aimed to assess whether serum 25-hydroxyvitamin D was associated with general/central obesity among US adolescents, and further to explore the mediatory impact of homeostasis model assessment of insulin resistance (HOMA-IR) on this association. Methods: This study is cross-sectional in design. Study adolescents were enrolled from the National Health and Nutrition Examination Survey (NHANES), 2011-2018. Serum 25-hydroxyvitamin D categories associated with general (indexed by body mass index) and central (indexed by waist circumference to height ratio) obesity were regressed. The possible mediatory effect of HOMA-IR on this association was explored. The nonlinear and dose-response association was examined by restricted cubic spline (RCS) test. Results: Total 2,696 adolescents were eligible for inclusion, and the mean age of all adolescents was 15.4 years. Overall, the percentage of general and central obesity was 38.0% and 38.6%, respectively. Compared with adolescents with sufficient vitamin D, adolescent with deficient and insufficient vitamin D intake were associated with general obesity and central obesity; fully-adjusted OR for general obesity was 1.602 (95% CI: 1.161 to 2.211) and 1.659 (1.385 to 1.986), and fully-adjusted OR for central obesity was 2.025 (1.445 to 2.837) and 1.557 (1.287 to 1.884), respectively, while there was no observable significance in adolescents with possibly harmful vitamin D. The proportion mediated by HOMA-IR was estimated to be 31.7% for global obesity and 50.3% for central obesity (both P<0.05). More stratified analyses were presented, and identified that the association with general obesity was particularly present among Mexican American, while with central obesity among Non-Hispanic Black adolescents. Conclusions: Our findings indicate that deficient or insufficient 25-hydroxyvitamin D concentrations were associated with the significant risk of general and central obesity among US adolescents, and approximately 30% and 50%, respectively, of these associations were mediated by HOMA-IR.